(untitled) (Global Journal of Human-Social Science, 2019)
Social progress and economic development are not possible by keeping women lag behind They should be given a level playing field to foster in their social and working life Representative bureaucracy theory suggests that increasing gender representation in civil service produces substantive benefits to the women in the broad society Moreover representative working groups can develop an empathetic understanding that is required to render gender-sensitive public service as well as womenfriendly working environment The present study has evaluated the role of gender representation in civil service to the wellbeing of women as clients in the society and employees in the organizations Based on the previous studies it reveals that gender representative bureaucracy is desirable to empower women in the society and organization through ensuring social security and developing the quality of working life Diversity in the workforce is essential for effective government performance The paper shows how representative bureaucracy works for the betterment of women and society and outlines the significance of women representation in civil service